Therapeutic strategies for KRAS G12C-mutant non-small cell lung cancer: from bench to bedside and beyond - Huang, Renjie; Gong, Xian; Du, Jianting; Xu, Guobing; Qian, Jiekun; Liao, Guoliang; Lin, Yuxing; Pan, Maojie; Zheng, Bin; Yuan, Wenjie; Huang, Qinzhao; Chen, Chun; et al. (Frontiers in Pharmacology, 2026)
KRAS is one of the most frequently mutated oncogenes in non-small cell lung cancer (NSCLC), particularly in lung adenocarcinoma, with mutation rates ranging from 15% to 25%. Historically considered “undruggable,” KRAS has recently become a viable therapeutic target with the development of selective KRAS G12C inhibitors such as sotorasib (AMG510) and adagrasib (MRTX849). These inhibitors have demonstrated promising clinical efficacy; however, their effectiveness is frequently limited by the emergence of resistance mechanisms. This review provides a comprehensive analysis of KRAS G12C structural biology, its role in oncogenic signaling, and the challenges associated with targeted therapy. We discuss the mechanisms of intrinsic and acquired resistance, current monotherapy limitations, and the rationale for combination strategies aimed at overcoming resistance. Additionally, we explore future therapeutic perspectives, including novel inhibitors, combination regimens, and emerging precision medicine approaches, to optimize treatment outcomes for patients with KRAS G12C-mutant NSCLC.